(untitled) (International journal of artificial intelligence, 2025)
This article discusses the names and functions of Jewish and Christian religious leaders as described in Ibn Khaldun’s “Muqaddima”. Although the “Muqaddima” is primarily considered a source on societal governance, it also contains information related to religious studies.